Job Rotation, Work Environment, and Civil-Service Educator Performance: The Mediating Role of Work Motivation - Putu Ita Widyantari Utami; I Nyoman Wijana Asmara Putra (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Persistent shortfalls in employee motivation at Udayana University are evident in behaviors reflecting a perceived lack of appreciation and a diminished commitment to assigned duties within an unconducive work environment. Addressing these concerns, this study investigates whether job mutations (i.e., rotations or transfers) and workplace conditions—individually and jointly—influence the performance of civil-service educational staff, and whether work motivation mediates these relationships. By integrating the constructs of mutation, work environment, motivation, and performance, the research offers faculty leaders actionable insights for fostering enthusiasm and enhancing work quality among civil servants. The analysis draws on questionnaire data from 214 civil-service educational personnel and employs Partial Least Squares Structural Equation Modeling (PLS-SEM, version 4) to test the proposed hypotheses. Results reveal that both mutations and the work environment exert significant positive effects on employees’ motivation and performance. Moreover, motivation directly enhances performance and functions as a significant mediator linking mutations and work environment to performance outcomes. These findings underscore the importance of strategically managed job rotations and supportive workplace conditions, together with targeted motivational interventions, in strengthening the performance of civil-service educational staff at Udayana University. Keywords: Mutation; Work Environment; Work Motivation; Performance.